Rethinking Cultural Keystone Practices: Conflict Resolution Practices as Examples of Salience and Well-Being - Arinyo-i-Prats, Andreu; LaTosky, Shauna; Turner, Nancy J. (Ethnobiology Letters, 2025)
We explore and expand on the concept of Cultural Keystone Practices as an extension of the concept of Cultural Keystone Species and Places. These concepts have helped raise awareness of traditional human-environment interactions by focusing on community well-being and salience. We discuss several keystone-related terms and link them as interdependent for well-being, where salience itself might fall within one keystone concept or another. We focus on three illustrative examples of Cultural Keystone Practices (tribunal de les aigües, Potlatch and dônga) which share conflict resolution as a well-being function. In these three cases, the salience resides in the practice itself, rather than in a particular place or species. Moreover, since the societies that host these practices perceive them as traditions that are not easily substituted with other ‘functional’ equivalents, we can consider them as keystones. Furthermore, we emphasize the need for an assessment strategy for these practices and highlight the limitations of other approaches for the direct and indirect protection of cultural practices, such as UNESCO’s Intangible Cultural Heritage (ICH). Cultural Keystone Practices can be a key enabler for people’s recognition of culture as essential for well-being. A standardized, cross-cultural, community-driven measurement of Cultural Keystone Practices has the potential to serve as a foundation for evaluating the risk of cultural loss associated with significant cultural practices, as well as the consequences of such loss, across diverse contexts.